Nitric Oxide Production in Professional Skiers During Physical Activity at Maximum Load - Parshukova, Olga I.; Varlamova, Nina G.; Bojko, Evgeny R. (Frontiers in Cardiovascular Medicine, 2020)
The purpose of this study is to assess the production of nitric oxide in professional cross-country skiers with normotensive and hypertensive responses to physical activity at maximum load. The observation group included professional cross-country skiers (22.2±7.1 years, n=107) who were current members of the national team of the Komi Republic. All the examined athletes performed the exercise test on a cycle ergometer “until exhaustion”. The following parameters were determined for each participant while they were sitting at rest, while at their anaerobic threshold level, during peak load and during the recovery period (5th minute): systolic blood pressure, diastolic blood pressure, heart rate, and the level of stable nitric oxide metabolites (nitrites, nitrates) in capillary blood samples. According to the blood pressure results, the cross-country skiers were divided into two groups. Group I included athletes with a normotensive response to stress. Group II was composed of individuals with a hypertensive response to stress. During the performance of the test “until exhaustion”, a significant (p<0.05) increase in the amount of stable metabolites of nitric oxide was observed in the group of athletes with a normotensive response to the load compared with the group with a hypertensive response to the load. In athletes with a normotensive reaction to the load during exercise at maximum loadand in the early recovery period, nitrate was prioritized in the regulation of vascular tone. The exercise test on a cycle ergometer “until exhaustion”, combined with the assessment of the levels of stable nitric oxide metabolites in plasma, can be considered a test for the early diagnosis of endothelial dysfunction in professional athletes.